Global changes in local ecosystem services in Alpine and Arctic regions in Europe (introduction) - Hausner, Vera Helene (2016)
Introduction from the European Ecosystem Services 2016 conference. Held from 19.09.16 - 23.09.16 in Antwerp. Arranged by the University of Antwerp/ESP partnership.